2010
DOI: 10.1111/j.1365-2044.2010.06455.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Can sugammadex save a patient in a simulated ‘cannot intubate, cannot ventilate’ situation?

Abstract: SummaryRecent studies have shown that the use of high dose rocuronium followed by sugammadex provides a faster time to recovery from neuromuscular blockade following rapid sequence induction than suxamethonium. In a manikin-based 'cannot intubate, cannot ventilate' simulation, we studied the total time taken for anaesthetic teams to prepare and administer sugammadex from the time of their initial decision to use the drug. The mean (SD) total time to administration of sugammadex was 6.7 (1.5) min, following whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 16 publications
0
44
0
6
Order By: Relevance
“…However, it does add considerable weight to the argument that confirmation is not necessary since neuromuscular blockade is known to facilitate tracheal intubation, and we have now shown that it facilitates mask ventilation as well. Clinicians still remain divided on this issue [5], and our hope is that our findings will add value to this important discussion. In relation to the first question, Broomhead et al divided anaesthetists using a questionnaire into 'checkers' (who assess the ability to mask ventilate the lungs before administering NBDs) and 'non-checkers' [3].…”
Section: A Replymentioning
confidence: 81%
See 1 more Smart Citation
“…However, it does add considerable weight to the argument that confirmation is not necessary since neuromuscular blockade is known to facilitate tracheal intubation, and we have now shown that it facilitates mask ventilation as well. Clinicians still remain divided on this issue [5], and our hope is that our findings will add value to this important discussion. In relation to the first question, Broomhead et al divided anaesthetists using a questionnaire into 'checkers' (who assess the ability to mask ventilate the lungs before administering NBDs) and 'non-checkers' [3].…”
Section: A Replymentioning
confidence: 81%
“…Note that in this context, rocuronium, with sugammadex if needed, is assumed to be akin to a short-acting NBD, although some evidence suggests that it may not be [5].…”
Section: A Replymentioning
confidence: 99%
“…Trotzdem befallen mich Zweifel, wie dieses Vorgehen im Fall eines Haftpflichtschadens bewertet wür-de. Denn, um im Notfall auch wirklich schnell genug 16 mg/kgKG injizieren zu können, muss Sugammadex vor der Narkoseeinleitung vorbereitet sein [3]. Damit ist Sugammadex Teil des Anästhesie-konzepts, das den Einsatz schon vor der Entwicklung des Kindes impliziert.…”
Section: Dünnes Juristisches Eisunclassified
“…Though sugammadex is not without problems, 19,20 data from phase 1-3 clinical trials as well as post-marketing data from millions of patients have shown that sugammadex is safe. There is only a rare risk (\ 1%) of anaphylactic reactions with sugammadex, and these are treatable with standard therapy.…”
mentioning
confidence: 99%
“…Bien que le sugammadex ne soit pas parfait, 19,20 les données d'études cliniques de phase 1-3 ainsi que les données recueillies depuis sa commercialisation chez des millions de patients démontrent que cet agent est sécuritaire. Il n'existe qu'un risque rare (\ 1%) de réactions anaphylactiques avec le sugammadex, et ces réactions sont traitables avec la thérapie usuelle.…”
unclassified